The Night Sky Companion A Yearly Guide to Sky-Watching 2009 - Plotner, Tammy; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2009)
The Night Sky Companion is far more than just an observing guide. It is a year's journey into the science and facts of astronomy and space travel, along with some of its history and the men and women who made it. If you're a sky watcher equipped with any kind of astronomical telescope, binoculars, or even just your eyes, you are sure to find this book fascinating and useful. Taking a day-by-day look at the sky over the course of the whole year, Tammy Plotner has assembled a digest to appeal to all amateur and practical astronomers, as well as "armchair" astronomers. In this book you'll find a wealth of information touching upon every aspect of your observations, including hwo to locate the object you're looking for, whether it's a meteor shower, a comet, a variable star, a crater on the Moon, or the remnants of a supernova. By the time the year is over, you'll be an expert on the skies-and ready to tackle yet another year of exciting projects!
January, 2009 -- February, 2009 -- March, 2009 -- April, 2009 -- May, 2009 -- June, 2009 -- July, 2009 -- August, 2009 -- September, 2009 -- October, 2009 -- November, 2009 -- December, 2009.
Keywords: PHYSICS; ASTRONOMY; PHYSICS; ASTRONOMY; POPULAR SCIENCE IN ASTRONOMY